A first comprehensive ecological approach on the highly endemic mygalomorph spider Mecicobothrium thorelli (Araneae: Mecicobothriidae): understanding life history traits to address future conservation issues. Issue 1 (17th January 2022) - Panchuk, Justina; Ferretti, Nelson
ABSTRACT: Mecicobothrium thorelli is a very small mygalomorph spider that exclusively inhabits native mountainous grasslands of southern South America (Argentina and Uruguay). Several aspects of the biology of M. thorelli are still unknown. The goal of this study is to provide knowledge about the ecology of this species in a threatened habitat for the first time, based on extensive field work carried out during one year. A total of 119 individuals were registered. The species was found to select large refuges (rocks) and avoid small refuges, while the temperature of these did not seem to influence refuge selection. Juveniles and adults represented 69.9% and 30.1% of the total, respectively. Juveniles were found throughout the whole sampling period, while females were found mostly in June and males were recorded in May (winter in the southern hemisphere). The spatial distribution was random on most dates, with the exception of June, July and May. Also, a regular spatial pattern was observed in June. Mecicobothrium thorelli has a wintery life cycle, increasing its abundance during the coldest months of the year, and chooses particular characteristics of the microenvironment, such as refuge size. It usually presents a random spatial distribution, except at smaller scales during the reproductive period.